Perancangan Dashboard Sistem Informasi Pemeringkatan UBAQA (UB Annual Quality Award) dengan Metode Human Centered Design - Dinda Aditama; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Various plans and strategies were made by Indonesian educational institutions to increase a quality of education, one of them is a work program from Brawijaya University called "UBAQA (UB Annual Quality Award)". UBAQA has goals to evaluate and appreciate all unit in Brawijaya that give a good services. In this case, a system needed to assist the work of UBAQA. In additional to existing features, the user experience is also important to improve usability system Designing user experience by applying information visualization so the information is easier to understand. The monitoring process can be more effective by designing an UBAQA information system dashboard. An approach that used in this research is human centered design, and used the elements of user experience for design phases. The design stages are context specifications, user needs analysis, design, and evaluation. Evaluation was done in 2 times, that is testing with user use Single Ease Questionnaire (SEQ) and expert use heuristic evaluation, From the evaluation result 17 interface problems were found, 8 of them are from user and 9 of them are from expert. After the evaluation phase, the author make improvements to the interface according to suggestions given. This research was done by three times iteration to meet user needs.